1972
DOI: 10.1021/ja00776a019
|View full text |Cite
|
Sign up to set email alerts
|

Chemical evolution of a nitrogenase model. V. Reduction of nitriles

Abstract: Nitrogenase model systems, composed of molybdate and thiol ligands such as, e.g., cysteine, catalyze the reduction of aliphatic nitriles to alkanes and NHa in the presence of NaBH4. The reaction is significantly stimulated by substrate amounts of ATP, is faster in DzO than in HzO, and is inhibited up to 90 and 41 %, respectively, by CO and Nz at 1 atm of partial pressure. Experiments with IeNz indicate that molecular nitrogen is reduced under these conditions, while CO apparently inhibits by forming a complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

1973
1973
2001
2001

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Our attempts to demonstrate a capability of the molybdenumglutathione complex to catalyze the reduction of N2 to ammonia failed. In our opinion, however, the recently reported reduction of N2 with a ratio of 0.004 mol of N2 reduced per mol of Mo-cysteine complex during a period of 48 hr (10) should not be regarded as a significant catalytic reduction of N2. In contrast, we emphasize that all the model chemical systems studied thus far lack the essential quality of nitrogenase, which is the efficient catalysis of the binding and reduction of N2 to NH3.…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…Our attempts to demonstrate a capability of the molybdenumglutathione complex to catalyze the reduction of N2 to ammonia failed. In our opinion, however, the recently reported reduction of N2 with a ratio of 0.004 mol of N2 reduced per mol of Mo-cysteine complex during a period of 48 hr (10) should not be regarded as a significant catalytic reduction of N2. In contrast, we emphasize that all the model chemical systems studied thus far lack the essential quality of nitrogenase, which is the efficient catalysis of the binding and reduction of N2 to NH3.…”
Section: Resultsmentioning
confidence: 64%
“…4. The highest specific activity was observed with 10 complex was added under comparable conditions. The specific activity of the complex decreased rapidly at concentrations of complex above 50 Mug in a reaction mixture of 3 ml.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The authors regard this system as a close model of nitrogenase, although under the optimal conditions the yield of ammonia is extremely small, reaching 0.06-0.1%relative to the initial molybdenum compound after five days at a nitrogen pressure of 140 atm. In later communications 143 ' 144 the authors reported that the results were confirmed with the aid of labelled nitrogen 15 N 2 . Acetylene inhibits the reduction of nitrogen, while carbon monoxide does not affect the yield of ammonia appreciably.…”
Section: The Reduction Of Nitrogen In Molybdenum-thiol Systemsmentioning
confidence: 86%
“…For example, in the reduction of isonitriles molybdate can be replaced by compounds of other transition metals (WO4", VOi", Pd 2 *, Rh , Ru 3+ , Co 3+ , and Fe 2+ ), some of which are more effective than molybdenum compounds 143 .…”
Section: The Reduction Of Nitrogen In Molybdenum-thiol Systemsmentioning
confidence: 99%